PELAKSANAAN EKSEKUSI OBJEK JAMINAN FIDUCIA TERKAIT PERATURAN KAPOLRI NOMOR 18 TAHUN 2011 - Inri Januar (Fakultas Hukum Universitas Kristen Indonesia, 2017)
IThe Fiduciary Guaranty Act provides benefits for fiduciary and fiduciary beneficiaries in carrying out economic activities. This law also provides legal certainty and guarantee to parties by execution of fiduciary merchandise without a court decision. The existence of regulation of the Chief of Police of the Republic of Indonesia further strengthen the protection of the State to the people who need security from the police. Execution in fiduciary warranty is defined as the sale of fiduciary goods either through public auction or under-sales. The collection of collateral goods is an activity to achieve the execution of fiduciary guarantee. The good faith of the debtor is an important role in preventing the occurrence of physical clashes in case of forced taking by creditors protected by the Act. Kata Kunci: Hak, Jaminan, dan Eksekusi